2019
DOI: 10.15403/jgld-344
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Arrhythmias and Electrocardiogram Modifications in Non-Alcoholic Fatty Liver Disease. A Systematic Review

Abstract: Background and Aims: Recent studies have evaluated the relationship associating non-alcoholic fatty liver disease (NAFLD) with several electrocardiogram (ECG) findings, but the results have been inconsistent. The aim of this systematic review is to assess the association between NAFLD with ECG modifications. Methods: We conducted a systematic search on PubMed with predefined keywords identifying observational studies published till 22 February 2019 with NAFLD diagnosed either by biopsy, imaging, surrogat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 46 publications
1
19
0
1
Order By: Relevance
“…21 ECG, which can be performed readily and repeatedly, and can be analyzed instantly, could be a candidate of a tool for predicting BA, because ECG parameters would vary according to individual age and gender. 5,6 Although ECG is mainly responsible for the circulatory and the respiratory system, several analyses have revealed that ECG can be affected by various extracardiac diseases: ventricular repolarization was altered by hemodialysis 22 ; prolonged QTc was observed in end-stage liver disease 23,24 and non-alcoholic fatty liver disease 25 ; ST segment and T wave can be altered in acute cholecystitis 26 ; ST depression, left ventricular hypertrophy, prolonged QTc, and T wave inversion were observed in patients with intracranial hemorrhage 27,28 and other ECG abnormalities were represented in patients with brain injury and stroke 27 ; higher heart rate, prolonged QTc, and low voltage appeared in patients with thyroid dysfunction. 29 The possible common mechanisms which connects the various systemic health status and ECG would be vascular status and autonomic nerve system, which would possibly be the key pathogenesis that accords aging.…”
Section: Clinical Implication Of Gap Between Ecg-predicted Ba and Camentioning
confidence: 99%
“…21 ECG, which can be performed readily and repeatedly, and can be analyzed instantly, could be a candidate of a tool for predicting BA, because ECG parameters would vary according to individual age and gender. 5,6 Although ECG is mainly responsible for the circulatory and the respiratory system, several analyses have revealed that ECG can be affected by various extracardiac diseases: ventricular repolarization was altered by hemodialysis 22 ; prolonged QTc was observed in end-stage liver disease 23,24 and non-alcoholic fatty liver disease 25 ; ST segment and T wave can be altered in acute cholecystitis 26 ; ST depression, left ventricular hypertrophy, prolonged QTc, and T wave inversion were observed in patients with intracranial hemorrhage 27,28 and other ECG abnormalities were represented in patients with brain injury and stroke 27 ; higher heart rate, prolonged QTc, and low voltage appeared in patients with thyroid dysfunction. 29 The possible common mechanisms which connects the various systemic health status and ECG would be vascular status and autonomic nerve system, which would possibly be the key pathogenesis that accords aging.…”
Section: Clinical Implication Of Gap Between Ecg-predicted Ba and Camentioning
confidence: 99%
“…NAFLD is a multisystem complex pathology without current approved therapies, primarily affecting the liver which causes modifications to the structure and function of the liver, leading to an increased liver-related morbidity and mortality from cirrhosis, liver failure, and hepatocellular carcinoma [5][6][7]. Moreover, an increasing body of evidence supports that NAFLD is not only a progressive liver disease, but can also lead to multiple systemic consequences and extrahepatic manifestations, including effects exerted on the cardiovascular system (CVS) [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Our findings suggested that the NST changes might represent an additional correlation with higher CVD risk in patients with NAFLD, and emphasized the importance of evaluating arrhythmic risk in NAFLD patients so as to strengthen early prevention and early intervention of CVD. Previous studies have demonstrated that there existed significant correlation between NAFLD and cardiac arrhythmias (Ismaiel et al, 2019), such as QTc prolongation (Targher et al, 2014), atrial fibrillation (Anstee et al, 2018), ventricular arrhythmias (Mantovani et al, 2016), but little attention was paid to explore the relationship between NST and NAFLD. Although, it has been suggested that NAFLD have adverse impact on ST segment elevation in myocardial infarction (Emre et al, 2015;Keskin et al, 2017) and NAFLD was correlated with silent myocardial ischemia (Lee et al, 2006), NST changes may be earlier signs of cardiovascular changes (Healy & Lloyd-Jones, 2016).…”
Section: Discussionmentioning
confidence: 99%